2021
DOI: 10.3389/fchem.2021.638187
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Peel Extract as an Inhibitor of SARS-CoV-2 Spike Binding to Human ACE2 Receptor (in vitro): A Promising Source of Novel Antiviral Drugs

Abstract: Plant extracts are rich in bioactive compounds, such as polyphenols, sesquiterpenes, and triterpenes, which potentially have antiviral activities. As a consequence of the coronavirus disease 2019 pandemic, caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus, thousands of scientists have been working tirelessly trying to understand the biology of this new virus and the disease pathophysiology, with the main goal of discovering effective preventive treatments and therapeutic agents. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 68 publications
(66 reference statements)
5
36
0
1
Order By: Relevance
“…The study reported that PUN was effective in suppressing human cytomegalovirus (HCMV) virus, herpes simplex virus (HSV-1), hepatitis C virus (HCV), respiratory syncytial virus (RSV), measles (MV) and dengue virus (DENV), at various concentrations without significant cytotoxicity [ 14 ]. Tito et al even reported in their study that PUN and EA inhibited the interaction between Spike protein and ACE2 and reduced viral 3CL protease activity in vitro, indicating the potential use of pomegranate extract as a prevention and treatment for SARS-CoV-2 disease [ 51 ].…”
Section: Pharmacological Effect Of Punicalagin and Metabolitesmentioning
confidence: 99%
“…The study reported that PUN was effective in suppressing human cytomegalovirus (HCMV) virus, herpes simplex virus (HSV-1), hepatitis C virus (HCV), respiratory syncytial virus (RSV), measles (MV) and dengue virus (DENV), at various concentrations without significant cytotoxicity [ 14 ]. Tito et al even reported in their study that PUN and EA inhibited the interaction between Spike protein and ACE2 and reduced viral 3CL protease activity in vitro, indicating the potential use of pomegranate extract as a prevention and treatment for SARS-CoV-2 disease [ 51 ].…”
Section: Pharmacological Effect Of Punicalagin and Metabolitesmentioning
confidence: 99%
“…Different examples are available in the literature, mainly based on the application of Virtual Screening (VS) procedures [ 6 ]. Of note are research articles that have reported data properly validated by in-silico protocols (e.g., docking calibration) and/or in vitro assays for the identification of: (i) inhibitors of the SARS-CoV-2 main and papain-like proteases [ 3 , 4 , 7 ]; (ii) compounds targeting the receptor-binding domain (RBD) of the spike SARS-CoV-2 protein [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, more recent studies indicate two other receptors involved in the SARS-CoV-2 attachment [ 8 ]: a transmembrane glycoprotein, CD147, localized on the surface of the host cell, and a chaperone heat shock protein, GRP78 [ 15 , 16 , 17 ]. Both could interact with several ligands as well as the RBD of the viral S protein, acting as multifunctional receptors for viral entry [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P l a n t s e c o n d a r y m e t a b o l i t e s (PSM) in plants help combat biotic stresses (microorganisms, insects, parasites) and abiotic stresses (temperature, pH, water activity, heavy metals). In addition, these PSMs are also useful for humans, so plant and plant parts are used as nutraceuticals, drugs, and foodstuffs [9][10][11] . Plant secondary metabolites (PSMs) exhibiting antiviral activities by disturbing the viral particle constituents such as protein, lipid envelope, and genetic materials such as DNA or RNA of a virus particle.…”
Section: Introductionmentioning
confidence: 99%